2017
DOI: 10.18632/oncotarget.15410
|View full text |Cite
|
Sign up to set email alerts
|

Small molecule inhibitor screening identifified HSP90 inhibitor 17-AAG as potential therapeutic agent for gallbladder cancer

Abstract: Gallbladder cancer (GBC) is a lethal cancer with poor prognosis associated with high invasiveness and poor response to chemotherapy and radiotherapy. New therapeutic approaches are urgently needed in order to improve survival and response rates of GBC patients. We screened 130 small molecule inhibitors on a panel of seven GBC cell lines and identified the HSP90 inhibitor 17-AAG as one of the most potent inhibitory drugs across the different lines. We tested the antitumor efficacy of 17-AAG and geldanamycin (GA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…Consequently, the role of HSP90 in ErbB downregulation by proteasome inhibitors was then addressed. Treatments with both HSP90 inhibitor [39] and bortezomib [23,24] have been shown to inactivate HSP90α and increase its protein level. Our data also showed that the expression of HSP90α, but not full-length HSP90β, slightly increased when the cells were treated by proteasome inhibitors (Figure 4A,B), which might be because HSP90α mediates the fast chaperon response, while HSP90β is required the long-term cellular adaptation [40].…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, the role of HSP90 in ErbB downregulation by proteasome inhibitors was then addressed. Treatments with both HSP90 inhibitor [39] and bortezomib [23,24] have been shown to inactivate HSP90α and increase its protein level. Our data also showed that the expression of HSP90α, but not full-length HSP90β, slightly increased when the cells were treated by proteasome inhibitors (Figure 4A,B), which might be because HSP90α mediates the fast chaperon response, while HSP90β is required the long-term cellular adaptation [40].…”
Section: Resultsmentioning
confidence: 99%
“…( Supplemental Table 6 ). These panels have been used to identify kinase dependence in models of gallbladder cancer, nasopharyngeal carcinoma, and by us in leukemia and HNSCC ( Weber et al 2017 ; Yuan et al 2017 ; Tyner et al 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…(Supplemental Table 6). These panels have been used to identify kinase dependence in models of gallbladder cancer, nasopharyngeal carcinoma, and by us in leukemia and HNSCC (Weber et al 2017;Yuan et al 2017;Tyner et al 2018). Whole-exome sequencing (Illumina Hi-Seq) was performed on the three cases of collected samples with a median coverage of 209×-213×.…”
Section: Functional Analysismentioning
confidence: 99%
“…Evidence of the activities of Hsp90 inhibitors has been obtained in vitro and in animal models, and numerous clinical trials (phase I-III) have been conducted to develop novel cancer treatments [ 2 5 ]. A number of phase II clinical trials have been performed on 17-allylamino-17-demethoxy-geldanamycin (17-AAG; a geldanamycin analog) and NVP-AUY922 (hereafter called AUY922; a purine-scaffold derivative and non-geldanamycin analog of 17-AAG) [ 6 9 ]. However, their therapeutic benefits were often limited by toxicity and resistance of cancer cells.…”
Section: Introductionmentioning
confidence: 99%